Penggunaan Standar Metode Work Breakdown Structure (WBS) Pada Proyek Pembangunan Gudang BPBD dan Rumah Jabatan Dandim - Soeparyanto, Try Sugiyarto; Nuhun, Ridwan Syah; Ismayana, Ismayana; Apriani, Meri; Hado, Hado (Universitas Sulawesi Tenggara, 2024)
In today's modern era, the construction of buildings stands as a crucial element in the development of infrastructure. Among the various methods utilized for managing such construction projects, the Work Breakdown Structure (WBS) has emerged as an effective tool. WBS serves as a project management technique, breaking down complex tasks into smaller, manageable components, thereby facilitating efficient planning, execution, and monitoring throughout the project lifecycle.This research employs the Earned Value Method (EVM) approach, chosen for its adeptness in quantifying project cost and time performance. By integrating three key dimensions - scope, schedule, and budget - EVM offers a comprehensive framework for evaluating project performance.The findings of this study reveal subpar cost and time performance in the construction of the BPBD Warehouse and Military District Commander's office building. Conversely, the construction of the Veterans Building demonstrates stable performance in both cost and time aspects.The observed impact of implementing WBS standards, particularly in the construction of the Veterans Building, proves instrumental in enhancing project control. The detailed breakdown of work items and the clearer identification of required resources streamline the planning of Purchasing Orders (PO), thereby facilitating cost management efforts.